Integrasi Nilai-Nilai Islam untuk Meningkatkan Karakter Toleransi dan Kejujuran di SDN 21 Selayo Tanang Bukit Sileh - Yurneli, Yurneli (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to describe efforts to enhance students' attitudes of tolerance and honesty through the teaching of Islamic values at SDN 21 Selayo Tanang Bukit Sileh. The Islamic values taught are not limited to religious knowledge in the cognitive domain but are also holistically integrated into students’ daily behavior, both inside and outside the classroom. This research employs a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation as data collection techniques. The findings indicate that consistent and contextual teaching of Islamic values, combined with role modeling, effectively fosters tolerant attitudes toward differences and builds students’ integrity in speech and behavior. Teachers play a crucial role not only as instructors but also as moral exemplars and facilitators of value-based learning. Moreover, a supportive school environment—characterized by a vibrant religious culture and positive social interactions—further reinforces the internalization of Islamic values among students. These findings affirm that Islamic value-based education plays a strategic role in shaping students' character, particularly in instilling tolerance and honesty from an early age. Therefore, it is essential for primary schools to continue developing holistic, value-oriented learning approaches in order to cultivate a generation that is morally upright, possesses strong integrity, and can live harmoniously in a diverse society.